Antibacterial Activity and Mechanism of Action of Black Pepper Essential Oil on Meat-Borne Escherichia coli - Zhang, Jing; Ye, Ke-Ping; Zhang, Xin; Pan, Dao-Dong; Sun, Yang-Ying; Cao, Jin-Xuan (Frontiers in Microbiology, 2017)
The aim of this study was to investigate the antibacterial activity of black pepper essential oil (BPEO) on Escherich coli, further evaluate the potential mechanism of action. Results showed that the minimum inhibition concentration (MIC) of BPEO was 1.0 μL/mL. The diameter of inhibition zone values were with range from 17.12 to 26.13 mm. 2 × MIC treatments had lower membrane potential and shorter kill-time than 1 × MIC, while control had the highest values. E. coli treated with BPEO became deformed, pitted, shriveled, adhesive and broken. 2 × MIC exhibited the greatest electric conductivity at 1, 3, 5, 7, 9, 11 and 13 h, leaked DNA materials at 4, 8, 12, 16, 20, 24 and 28 h, proteins at 4, 6, 8, 10, 12, 14 and 16 h, potassium ion at 0, 0.5, 1, 1.5 and 2 h, phosphate ion at 0.5, 1, 1.5 and 2 h and ATP (P < 0.05); 1 × MIC had higher values than control. BPEO led to the leakage, disorder and death by breaking cell membrane. This study suggested that the BPEO has potential as the natural anti-bacterial agent in meat industry.